Bioremediation of polycyclic aromatic hydrocarbons (PAHs) present in biomass fly ash by co-composting and co-vermicomposting - Košnář, Zdeněk; Wiesnerová, Lucie; Částková, Tereza; Kroulíková, Stanislava; Bouček, Jiří; Mercl, Filip; Tlustoš, Pavel (Journal of hazardous materials, 2019)
An experiment was established to compare composting and vermicomposting for decreasing the content of polycyclic aromatic hydrocarbons (PAHs) in biomass fly ash incorporated into organic waste mixtures. PAH removal from the ash-organic waste mixture was compared to the same mixture spiked with PAHs. The removal of 16 individual ash PAHs ranged between 28.7 and 98.5% during the 240 day experiment. Greater dissipation of total PAH content of ash origin was observed at the end of composting (84.5%) than after the vermicomposting (61.6%). Most ash PAHs were removed similarly to spiked PAHs through the composting and vermicomposting processes. Higher manganese peroxidase in composting treatments indicated increased activity of ligninolytic PAH-degrading microorganisms. 3D models of total PAH removal were parametrized using the polarity index and organic matter content, and paraboloid equations for each treatment were estimated (all R2 > 0.91). A two-phase model of pseudo-first order kinetics analysis showed faster PAH removal by higher rate constants during the first 120 days of the experiment. The compost and vermicompost produced from the bioremediation treatments are usable as soil organic amendments.
Keywords: Enzyme activities; Biodegradation; polycyklické aromatické uhlovodíky; Lipase; Sewage; biodegradace; Elemental analysis; Soil Pollutants; látky znečišťující půdu; Peroxidases; půda; Polycyclic Aromatic Hydrocarbons; popel uhelný; zvířata; Coal Ash; Biodegradation, Environmental; biomasa; Kinetics; PAHs; odpadní vody; Composting; kompostování; First–order kinetic; Animals; Soil; peroxidasy; Biomass; kinetika; Oligochaeta; lipasa